Passive ground cooling system for low energy buildings in Malaysia (hot and humid climates) - Sanusi, Aliyah Nur Zafirah; Shao, Li; Ibrahim, M. Najib (Elsevier, 2012)
This paper presents an investigation of Earth Pipe Cooling Technology, conducted in a university campus in Malaysia. It was intended to seek for a passive cooling alternative to air-conditioning. The technology, where the ground was used as a heat sink to produce cooler air, has not been investigated systematically in hot and humid countries. In this work, air and soil temperatures were measured. At 1 m underground, the result is most significant, where the soil temperature is 6 °C and 9 °C lower than the maximum ambient temperature during wet and hot and dry season, respectively. Polyethylene pipes were buried around 1.0 m underground and temperature drop between pipe inlet and outlet were compared. A significant temperature drop was found in these pipes: up to 6.4 °C and 6.9 °C depending on the season of the year. The result shows the potential of Earth Pipe in providing low energy cooling in Malaysia. © 2012.